A new species of milk frog of the genus Trachycephalus tschudi (anura, hylidae) from the amazonian rainforest - Gordo, Marcelo; Toledo, Luis Felipe; Suárez, Pablo; Kawashita-Ribeiro, Ricardo Alexandre; Ávila, Robson Waldemar; Morais, Drausio Honório [UNESP]; Nunes, Ivan (Herpetologists League, 2013)
We describe a new species of Trachycephalus from the Amazon Rain Forest, which is morphologically similar to T. resinifictrix (Goeldi). This new species is characterized by a medium body size for species in the genus (males snout-vent length [SVL] 57.9-74.3 mm, females SVL 74.4-84.9 mm); skin of the head not co-ossified with underlying dermal bones; dorsal skin texture, including that of the head, densely glandulous with several tubercles; paired vocal sac that protrudes at a posterior angle to the jaw when inflated; iris coloration pinkish-beige with a horizontal black bar and a vertical thin black line below the pupil; dorsal color pattern consisting of a wide interocular whitish-beige and a dark blotch on the middle of the dorsum joining the crossbar at the top of the dorsum, forming a T shape; rounded snout in dorsal view, and rounded or acuminate in profile; well-developed supratympanic fold; ulnar tubercles present, sometimes associated with ulnar fold; well-developed axillary membrane; well-developed tarsal fold; males with nonhypertrophied forearm; minimum frequencies of the advertisement call lower than 0.38 kHz; pulse rate 126.7-146.6 pulses/s; tadpole external coloration with brown reticulated blotches in the superior portion of the fin; tooth row formulae 2(2)/4. The new species, which is widely distributed in the Amazonian Forest, has been confused with the parapatric T. resinifictrix. It is a canopy treefrog that breeds in tree-holes that have accumulated rainwater. © 2013 by The Herpetologists' League, Inc.
Keywords: Canopy treefrog; Hylinae; Lophiohylini; Taxonomy; Trachycephalus cunauaru; Trachycephalus resinifictrix; Tree-holes